Kilka uwag o ochronie infrastruktury krytycznej w świetle przepisów ustawy o zarządzaniu kryzysowym i ustawy o „złotej akcji” Skarbu Państwa - Floriańczyk-Kardas, Monika (Kwartalnik Prawa Publicznego, 2015)
In general, critical infrastructure shall be understood as objects, facilities, networks, services and assets which, if disrupted or destroyed, would have a serious impact on the health, safety, security or economic well-being of citizens or the effective functioning of the state. The protection of national critical infrastructures is nowadays considered a paramount objective by all modern countries around the world. As of today, there is no universal recognized definition of critical infrastructure, this article provides an overview of the most common definitions. As in Poland critical infrastructure can be owned or operated by both the public and the private sector, the article identifies also all legal entities which are obliged to protect it as well as the detailed scope of their duties. The article presents also the legal techniques provided in the Crisis Managment Act and „Golden Share” Act, that can be applied to critical infrastructure protection. As protecting and ensuring the continuity of operation of critical infrastructure assets are vital to national security, public health and safety, economic vitality, this article includes the assessment of the polish regulation in terms of concerns as for its application in practice.